The Proximate Content of Mackerel Fish (Scomberomorus commerson) with Different Drying Methods - Maulid, Deden Yusman; Putra, Ronald Septiawan; Nusaibah, Nusaibah; Abrian, Satriya; Pangestika, Widya; Arumsari, Kusuma; Yuniarti, Endah (Agrikan Jurnal Agribisnis Perikanan, 2021)
Fish skin is one of kind by-products of the fillet industry and the fish processing industry. Mackerel skin has not been used optimally, although it has good economic potential and has high nutritional content. This study aims to obtain the best drying method based on the proximate content produced in mackerel fish skin chips. The drying method used are natural drying using sun dried and artificial drying method using oven dried. The parameter observed was the proximate content of mackerel chips. The proximate content was obtained using the AOAC(2005) method. The results of the proximate test on mackerel skin chips with oven drying method are: the value of water content 12.85%, ash content of 16.12%, fat content of 17.74%. Carbohydrates 24,00%, Protein content 28,91%. While the proximate value using the sun drying method contains 9.21% moisture, 6.73% ash content, 17.74% fat content, 40.66% carbohydrates, and 29.95% protein content. The best drying method is obtained by sun dried method because it gives the smallest moisture (9.21%) and the highest protein content (29.95%).